"Olha!.. Arru(a)ção !?..." A ação clínica no viver cotidiano: conversação com a fenomenologia existencial. - Santos, Suely Emília de Barros (2016)
This study was born from some experienced professional practice uncertainties while facing tensions appeared between theory and practice, as well among experience and the many Psychology epistemological referential, as acting in different institutional/social contexts. The research main goal, departing from psychologists‟ practice, proposes a comprehension of how happens the clinical action into the quotidian life. It starts by comprehending the clinical action into daily life as a psychologist‟s proper mode to intervene before demands that emerge from the quotidian in collective habited spaces. The scenery was Bom Jesus Hill, in Caruaru city, a rural area in Pernambuco state. The protagonists were Psychology professionals who work by the Heidegger‟s existential phenomenology perspective, as well as clients who were assisted by those collaborators and other psychologists. Experience was the prime source for a comprehensive pro-duction. Its path was taken as method for an interventive research, by dialoging with some Heidegger´s existential analysis as well as Gadamer‟s philosophical hermeneutics presupposed as epistemological perspective. The clinical cartography crossed all the study, guided by the question: how the psychologists‟ clinical action in an existential phenomenological comprehension may occur in daily living; therefore, the present research may be seeing as a cartographical thesis. The philosophic-comprehensive mark come into the thesis in a dialogue with “the raw material”, taken from conversation panels with three psychologists and six clients and from the researcher‟s diaries, meanwhile the phenomenon was being illuminated by the dialogue with some philosophers and psychologists. The comprehensive analysis followed Critelli‟s sense analytics and Gadamer‟s philosophical hermeneutics. It was revealed that the clinical action in quotidian living while in collective habited spaces shows how the psychologist takes path by following the errant client that transits by landscape marked by daily occurrences. His setting is open as acquaintanceship spaces with many stations. It is necessary to be available to listen in action demands that come from the population. By being always open makes possible to him to harvest the existence suffering as well the modes of cohabiting collective spaces, by assuming, in one hand, that the clinical action flows together with political, educational, ethical and aesthetical actions, that claim for his own responsibility as well for the others and the world; on the other hand, he perceives that it is vital to cope with the diversity of psychological practice modalities, which show how unpredicted is each daily situation before his art craft.